2020
DOI: 10.1136/bmjopen-2019-036746
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and predictors of mortality among children admitted to the pediatric intensive care unit at the University of Gondar comprehensive specialised hospital, northwest Ethiopia: a prospective observational cohort study

Abstract: ObjectiveTo determine the incidence and predictors of mortality among children admitted to the paediatric intensive care unit (PICU) at the University of Gondar comprehensive specialised hospital, northwest Ethiopia.DesignA single-centre prospective observational cohort study.ParticipantsA total of 313 children admitted to the ICU of the University of Gondar comprehensive specialised hospital during a one-and-a-half-year period.MeasurementsData were collected using standard case record form, physical examinati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
27
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 22 publications
8
27
3
Order By: Relevance
“…In the current study, the analysis showed that majority 175 (57.4%) of children admitted to the PICU were males and under 5 years of age contributing more than half of the admission. This finding is comparable with a study done in Ethiopia and elsewhere [11][12][13][14] . And majority of patients were found in the age group of 10-14 years which is similar with a study done in Ethiopia [5] .…”
Section: Discussionsupporting
confidence: 91%
“…In the current study, the analysis showed that majority 175 (57.4%) of children admitted to the PICU were males and under 5 years of age contributing more than half of the admission. This finding is comparable with a study done in Ethiopia and elsewhere [11][12][13][14] . And majority of patients were found in the age group of 10-14 years which is similar with a study done in Ethiopia [5] .…”
Section: Discussionsupporting
confidence: 91%
“…In this study, patients who were receiving mechanical ventilation had a threefold higher risk of passing away than those who were not. According to a research conducted in Gondar, Ethiopia, patients who require MV have a death rate that is 2.36 times greater than those who do not, 32 and this result is in line with that finding. In a similar vein, an Italian study indicated that patients who did not require MV had a better likelihood of surviving after being admitted to the PICU (100% vs 26.1%, P 0.001).…”
Section: Discussionsupporting
confidence: 72%
“…But we found significantly low mortality in studies with larger sample size when compared with studies of smaller sample size. Mortality in PICU varies from 2 to 30% across countries based on availability of resources and common diseases leading to ICU admissions [ 41 44 ]. The present analysis also showed that mortality among MIS-C patients increases by 4.68 times if the patients develop AKI.…”
Section: Discussionmentioning
confidence: 99%